Remote sensing science for the nineties : IGARss '90, Washington, DC : 10th Annual International Geoscience and Remote Sensing Symposium, May 20-24, the University of Maryland - International Geoscience and Remote Sensing Symposium n(10th : 1990 : University of Maryland at College Park); Mills, Ronnie (New York : Institute of Electrical & Electronics Engineers, 1990)
25